The Influence of Green Marketing, Attribute Tourism Products, E-Wom The Visit Decision - Muhammad Syarif Hidayatullah Elmas (International Journal of Social Science and Business, 2019)
The research was done in Probolinggo aimed at to investigate the influence among variables green marketing, attribute tourism products, and e-wom on the variables of decision visit tourism objects in Probolinggo. The model of the research uses quantitative with a descriptive model. A values that is green marketing, attribute tourism products, and e-wom as the independent variable and decisions visit as dependent variable. A population that is used all visitors tourism objects in Probolinggo on October 2018 with samples from 80 people. The determination use random sample of sampling. The result of the research show significance value of green marketing is 0,003, attribute tourism products is 0,000, and e-wom is 0,690. So that variable green marketing, attribute tourism products significant its impacts to decision visit, while e-wom influential insignificant of the decision visit